Thermodynamic analysis of a cascade organic Rankine cycle power generation system driven by hybrid geothermal energy and liquefied natural gas - Pan, Zilin; Fu, Yufei; Chen, Hongwei; Song, Yangfan (Frontiers in Energy Research, 2024)
The combination of renewable energy and liquefied natural gas (LNG) cold energy can effectively improve energy utilization efficiency and achieve the goal of energy conservation and emission reduction, which is one of the important directions of future development. This work proposed a cascade organic Rankine cycle (ORC) driven by a geothermal heat source and an LNG heat sink. Seven organic fluids are chosen as candidates to form different working fluid pairs. The effects of the main design parameters on system performance are carried out through the thermodynamic analysis. Then, the optimal design conditions and fluid selection schemes are searched based on the single-objective optimization results. Finally, the exergy destruction study is conducted under the optimal design conditions and working fluid pair. Results showed that the cascade ORC system using the working fluid pair of R601/R290 had the highest exergy efficiency, which could reach 20.02%. At the same time, under the optimal design conditions, the secondary cycle condenser and LNG direct expansion brought high exergy destruction, which was respectively 29.3% and 25.8%, and followed by the two turbines in the cascade ORC system, which were 16.1%, 11.2% and 7.7%.